ON STABILIZATION OF DISCRETE-TIME 2-D SYSTEMS IN ROESSER MODEL - Van Cuong, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This paper focuses on the stabilization problem of discrete 2-D linear systems described by the Roesser model. A tractable stability condition in terms of linear matrix inequalities is first reformulated. Then, two controller design schemes are developed to formulate stabilization conditions via state-feedback controllers (SFCs) and event-triggered controllers (ETCs). Numerical examples with simulations are given to illustrate the effectiveness of the design conditions.